ANALISIS PERSEPSI MASYARAKAT TERHADAP PENTINGNYA PENDIDIKAN TINGGI BAGI KAUM PEREMPUAN DI DESA BAIPAJUNG TANAH MERAH BANGKALAN - zubaida; Dian Eka Indriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Education is a conscious effort to pass on culture from one generation to the next. However, there is still a negative view of higher education for women, which is based on the general perception that "women do not need to pursue higher education because in the end they will only deal with housework. Therefore, this study was conducted using a qualitative descriptive method with a case study nature regarding public perception regarding the importance of education for women. The results of the study show that public perception of women who continue and the importance of higher education for women in Baijapung Village is going well. The people of Baipajung Village even tend to be proud if one of their children succeeds in continuing and completing their education at the higher education level. However, there is a different situation when families are faced with economic limitations that tend to set aside higher education for their daughters and prefer to get married immediately to ease the economic burden on their parents. There are inhibiting factors for women to be able to continue their education at university level such as economic limitations, expensive education costs, and the domino effect of economic limitations that make women prefer to work rather than having to continue their education